Penerapan Pencegahan Gangguan Mental Pada Remaja - Indah Nurul Ismi; Usiono Usiono (JOURNAL SAINS STUDENT RESEARCH, 2025)
The purpose of this research to reduse mental disorder in adolescentes.This research data that has been carried out.Implementing prevention of mental disorders is very important so that teenagers become good young people.